2022
DOI: 10.21037/atm-21-6618
|View full text |Cite
|
Sign up to set email alerts
|

Oligoadenylate synthetases-like is a prognostic biomarker and therapeutic target in pancreatic ductal adenocarcinoma

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is fatal cancer that causes death. Early metastasis, resistance to chemotherapy, and lack of treatment contribute to a poor prognosis. Therefore, finding new therapeutic targets and biomarkers is a particularly urgent need to improve the survival of PDAC patients.Oligoadenylate synthetases-like (OASL), an antiviral enzyme produced by interferon (IFN), has been found to be associated with the occurrence and development of multiple cancers. However, its role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…High OASL expression is associated with poor prognosis in patients with PDAC. 17 OASL may interact with ADAR to promote the proliferation and migration of breast cancer cells. 30 However, the effect of OASL on the progression of STAD has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High OASL expression is associated with poor prognosis in patients with PDAC. 17 OASL may interact with ADAR to promote the proliferation and migration of breast cancer cells. 30 However, the effect of OASL on the progression of STAD has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, high OASL expression is associated with poor prognosis in breast cancer and pancreatic ductal adenocarcinoma. 16,17 However, the role of OASL in STAD remains elusive and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research showed that OASL played an immune‐related role in cancers and viral infections. OASL −/− mice demonstrated increased IFN production and enhanced the cytotoxic function of CD8 + T cells and NK cells 74,75 . In addition, the PGE2/PTGES pathway plays a key role in inflammation 76 .…”
Section: The Root Of Actinidia Chinensis Planch In Cancer Immunitymentioning
confidence: 99%
“…OASL −/− mice demonstrated increased IFN production and enhanced the cytotoxic function of CD8 + T cells and NK cells. 74,75 In addition, the PGE2/PTGES pathway plays a key role in inflammation. 76 Studies revealed that PTGES/PGE2 signaling protected tumour cells against T-cell cytotoxicity and recruited MDSCs to the tumour microenvironment.…”
Section: Acroots and Potential Immune-related Genesmentioning
confidence: 99%